2022
DOI: 10.1007/s42399-022-01251-9
|View full text |Cite
|
Sign up to set email alerts
|

Bordetella pertussis, Chlamydia pneumoniae, and Mycoplasma pneumoniae Findings in Children During COVID-19 Pandemic in Finland

Abstract: Social restrictions effectively interrupted the typical respiratory virus circulation. The aim of this report is to describe how atypical pneumonia bacteria detections have changed during the COVID-19 pandemic in Finnish children. Bordetella pertussis, Chlamydia pneumoniae, and Mycoplasma pneumoniae findings were gathered from the National Infectious Diseases Register from 2015 to 2021 and stratified into three age groups (0–4, 5–9, and 10–14 years). Incidences per 100,000 children were calculated and 2020 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
1
0
2
Order By: Relevance
“…Studies conducted in other countries during the pandemic confirmed changes in the epidemiology of respiratory pathogens after the introduction of the above-mentioned restrictions (9)(10)(11)(12). In England, the number of laboratory tests for Bordetella pertussis infection and the percentage of positive tests were analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted in other countries during the pandemic confirmed changes in the epidemiology of respiratory pathogens after the introduction of the above-mentioned restrictions (9)(10)(11)(12). In England, the number of laboratory tests for Bordetella pertussis infection and the percentage of positive tests were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…W badaniach przeprowadzonych w okresie pandemii w innych krajach potwierdzono zmiany w epidemiologii patogenów układu oddechowego po wprowadzeniu w/w ograniczeń (9)(10)(11)(12). W Anglii przeanalizowano liczbę wykonanych testów laboratoryjnych w kierunku zakażenia Bordetella pertussis oraz jaki procent stanowią testy dodatnie.…”
Section: Discussionunclassified
“…Неблагоприятного прогноза и исходов сочетанных инфекций у детей при COVID-19 с M. pneumoniae в большинстве обзоров не зафиксировано [38]. Некоторые зарубежные авторы указывают на утяжеление течения COVID-19 в сочетании с РМ у взрослых, связывая данный феномен с гипериммунным ответом к обоим инфекциям, с преимущественным повышением sIgA [28].…”
unclassified